Pelaksanaan Asesmen Dan Hambatannya Di Taman Kanak-Kanak Kecamatan Medan Area Berdasarkan Kurikulum Merdeka - Aisiyah Aminy Siregar; Anita Yus (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
This research aims to describe the stages of implementing assessments based on the independent curriculum that have been implemented by kindergarten teachers in the Medan Area District and describe teacher obstacles in implementing assessments based on the independent curriculum by kindergarten teachers in the Medan Area District. The research method used is descriptive quantitative research with a non-experimental type. The results of the research findings are based on questionnaire calculations of the stages of assessment implementation based on the independent curriculum. The highest average score in the aspect is in the assessment reporting aspect, namely 3.4 in the good category. Then the second highest was in the aspect of preparing tools, setting criteria, and collecting data with an average of 3.3 in the good category. And the aspect with the lowest average is in the aspect of determining the value, namely 2.9 in the quite good category. The most common obstacle to implementing assessments based on the independent curriculum is limited time in collecting data, including giving children assignments that have not been completed in one day, so that teachers have not been able to collect children's assignments and have to wait until all assignments have been completed before they can be assessed. Then the least obstacle is the aspect of setting criteria where teachers still experience problems in distinguishing which children's assessment criteria are included in good criteria and which are included in proficient criteria